An evaluation of the recourse available to taxpayers where SARS does not adhere to the correct tax administrative procedures - Herbert, Lauren Stacey (Department of Finance and Tax, 2020)
There is a common perception among South African taxpayers and tax professionals that the South African Revenue Service (“SARS”) is “draconian” in its administrative actions and interactions with taxpayers and tax professionals, which infringes on taxpayers’ constitutional right to just administrative action. This dissertation aims to make taxpayers and tax professionals more aware of their right to just administrative action which entitles taxpayers to administrative action and interactions with SARS that are lawful, reasonable and procedurally fair. Furthermore, this dissertation investigates how taxpayers and tax professionals may go about defending such administrative rights, should SARS infringe upon it without just cause. A comparison is made between the recourse available to South African taxpayers and tax professionals who experience tax administrative disputes against SARS, against the recourse provided in a selection of foreign jurisdictions. This comparison is performed with a view to determine possible areas of improvement to the recourse provided in South Africa, as it pertains to administrative disputes against SARS. Recommendations to introduce a Taxpayers Bill of Rights or revise and improve on the current SARS Service Charter, is considered in Chapter 5 of this dissertation. This dissertation shows that while the introduction of the Tax Ombud in South Africa certainly enriched taxpayers’ constitutional right to just administrative action, the Tax Ombud’s limited authority, mandate and the non-binding effect of its recommendations on SARS, limits the effectiveness of the role of the Tax Ombud in South Africa. Recommendations to further the Tax Ombud’s authority and mandate are considered in Chapter 5 of this dissertation.